Project-Based IPAS Learning to Support Sustainable Development Goals (SDGs): A Literature Review on Implementation and Impact on Environmental Awareness of Elementary School Students - Silfi Melindawati; E. Kus Eddy Sartono; Wuri Wuryandani; Fatia Fatimah (Postgraduate, University of Mataram, 2025)
Project-Based Learning (PjBL) in IPAS (Ilmu Pengetahuan Alam dan Sosial) has emerged as a promising pedagogical approach to integrating Sustainable Development Goals (SDGs) into elementary education. This literature review synthesizes recent studies (2021–2025) on the implementation of PjBL in IPAS and its impact on environmental awareness among elementary school students. The review reveals that PjBL fosters active learning, critical thinking, and problem-solving skills by engaging students in real-world environmental projects such as waste management, biodiversity conservation, and eco-campaigns. These activities align with SDG 4 (Quality Education), SDG 13 (Climate Action), and SDG 12 (Responsible Consumption and Production). Findings indicate that PjBL significantly enhances students’ understanding of sustainability issues and promotes pro-environmental behaviors. The study concludes that PjBL-IPAS learning offers a transformative pathway to cultivating environmentally conscious citizens and advancing the SDGs through foundational education.